Geomorphological evidence of carbonate build-up demise on equatorial margins: A case study from offshore northwest Australia. (June 2019) - Van Tuyl, James; Alves, Tiago; Cherns, Lesley; Antonatos, Georgios; Burgess, Peter; Masiero, Isabella
Abstract: The demise of Miocene carbonate build-ups in the Browse Basin, Northwest Australia, has been explained as relating to geological and oceanographic processes. These include accelerated tectonic subsidence driven by subduction, ocean cooling following the mid-Miocene climate optimum, nutrient excess, poisoning by sediment drifts and local erosion driven by current winnowing, occurring discretely or simultaneously. Here, we critically assess the evidence for these different mechanisms using a combination of high-resolution 3-D seismic data, regional 2-D seismic profiles, and numerical stratigraphic forward modelling. Seismic interpretation and numerical modelling found that the proposed uniform subsidence rate of 125 m/Ma between 16.5 Ma and 5.33 Ma for the northern Browse Basin (Belde et al., 2017), when combined with the published estimate of eustatic sea level in Miller et al. (2005), was insufficient to drown the Miocene carbonate sequence and generate the geomorphological changes (barrier reef to isolated carbonate build-ups) observed on seismic data. Instead, a subsidence profile comprising pulses of rapid and slow subsidence is required. Significantly, our results suggest that subsidence rates exceeded 400 m/Ma in the northern Browse Basin, and that parts of the basin record the accumulation of sediment drifts. These sediment drifts are interpreted to have buried some carbonate build-ups, while suspended sediment reduced light transmissivity, inhibiting carbonate production. Thus, we postulate that current activity and excess nutrient supply are key, but often overlooked, oceanographic processes that lead to the demise of carbonate build-ups. Highlights: Current models regarding Miocene eustatic sea-level and subsidence are reviewed in the northern Browse Basin, NW Australia. Alternating pulses of rapid and slow subsidence are required to attenuate the Miocene eustatic sea-level changes. Environmental deterioration was the key to the demise of the Miocene carbonate sequence in the northern Browse Basin. Sediment drifts buried some carbonate build-ups and reduced light transmissivity, inhibiting carbonate production. CarboCAT modelling is effective in deriving the relative importance of time-variable processes on carbonate-reef growth.